Preventive Metabolic Medicine in Primary Care - Tint Swe Latt,; Madhur Verma,; Nitin Kapoor,; Sanjay Kalra, (Journal of the Pakistan Medical Association, 2025)
The responsibility, and right, of promoting metabolic health, and preventing metabolic disease, is that of the primary care physician. This communication lists the facets of metabolic care in a simple (Seven Rs) manner, connecting them with the various levels of prevention. All individuals should be counselled about regulation of lifestyle and mindstyle (primordial prevention). Those at risk of metabolic disease should reduce/redistribute their energy intake, and rescue overburdened storage system by using energy through exercise (primary prevention). Persons with established disease will need physio-friendly therapy to replenish and restore the physiological buffering of the body (secondary prevention). In persons with target organ damage, resilience of organ- systems can be enhanced, and existing damage repaired, by using modern drugs (tertiary prevention). Quaternary prevention and quinary prevention must be practiced. Reframing the Rs of preventive metabolic medicine, using the rubric of levels of prevention, will make this discipline more appealing to all. Keywords: Community medicine, diabetes, family medicine, obesity, prevention, primary health care